Household finance - Francisco J. Gomes; Michael Haliassos; Tarun Ramadorai (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2020)
There is increasing interest in applying lessons learned from household finance to the design of regulation, both within and across international borders. However, household financial decisions are complex, interdependent, and heterogeneous, and central to the functioning of the financial system. The authors present an overview of the rapidly expanding literature on household finance, beginning with the theory and empirics of asset market participation and asset allocation over the lifecycle. They discuss household choices in insurance markets, trading behavior, decisions on retirement saving, and financial choices by retirees and survey research on liabilities, including mortgage choice, refinancing, and default, and household behavior in unsecured credit markets, including credit cards and payday lending. They also connect the household to factors such as its social environment, cultural and hereditary factors, and financial literacy and suggest directions for future research.
urn:nbn:de:1685493912
Keywords: G50; 330; household finance